Enhanced chemotherapy response in hepatocellular carcinoma: synergistic effects of miR-122 and doxorubicin co-delivery system inducing apoptosis and DNA damage - Xiuyun Lin; Jie Liu; Guangfeng Wu; Xiu Yang; Wenqiang Yan; Nanfeng Fan; Hui Li (Cancer Nanotechnology)
Abstract Background Cancer cells can resist chemotherapy through various mechanisms, diminishing treatment outcomes. Research had indicated that combining miR-122 with doxorubicin (DOX) can improve hepatocellular carcinoma (HCC) therapy. Results To explore this, we created a one-pot co-delivery system, Fe-miR-122/DOX, by coordinating miR-122, DOX, and FeII ions into nanoparticles. These nanoparticles display uniform particle sizes, well-defined morphology, and exceptional colloidal stability in 10% FBS and 20% FBS solution over 24 h. When the ratio of DOX to miR-122 was set at 20:1, the loading efficiency of both drugs reached 54.7% and 55.5%, respectively. Cell experiments confirmed that Fe-miR-122/DOX efficiently delivers both miR-122 and DOX, enabling cytoplasmic delivery through lysosomal escape, facilitated by the positive charge of the nanoparticles. Functionally, miR-122 increases intracellular accumulation of DOX by downregulating P-glycoprotein (P-gp) expression, and it promotes apoptosis by downregulating B-cell lymphoma 2 (Bcl-2), which leads to the upregulation of Caspase-3. Additionally, Fe-miR-122/DOX disrupts cIAPs-mediated anti-apoptotic signals, downregulates PARP-1 expression, hinders DNA repair, promotes DNA fragmentation, enhances caspase-3 expression, and triggers programmed cell death, synergistically enhancing its antitumor efficacy. This synergistic mechanism disrupts DNA repair, amplifying DNA damage and apoptosis. Our cytotoxicity and apoptosis assays (with a HepG2 cell apoptosis rate of 85.98%) demonstrated the potent antitumor capability of Fe-miR-122/DOX. Conclusions This innovative system has demonstrated good biocompatibility and has the potential to transform HCC therapy. Future research could focus on optimizing the co-delivery system and assessing its efficacy in clinical trials.